1998
DOI: 10.1159/000010047
|View full text |Cite
|
Sign up to set email alerts
|

Single Fetal Demise in a Twin Gestation: Umbilical Vein Thrombosis

Abstract: Background: Single fetal demise in a twin pregnancy is a rare event, the common causes being twin-twin transfusion syndrome, chromosomal or congenital anomalies and abnormalities of the umbilical cord and placenta. Umbilical vein thrombosis is a very rare cause of single fetal demise in twins. Case: Three days after a reassuring biophysical profile, a 40-year-old primigravida with twin pregnancy presented at 38 weeks’ gestation in early labor when demise of 1 of the twins was recognized. She underwent a cesare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It has been reported that in twin pregnancies the incidence of the death of a twin during the second trimester is 0.5-6.8%, and the rate of mortality and morbidity resulting from the death of a twin is 23-46%. 6 Major complications that may arise in the mother and the surviving fetus are disseminated intravascular coagulation, neurological and nephrological damage, and premature delivery and birth. 2 It is known that sudden hypotension in the dead fetus can trigger damage in the organ systems, notably the nervous system of the surviving twin in connection with the placental blood flow to the dead fetus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in twin pregnancies the incidence of the death of a twin during the second trimester is 0.5-6.8%, and the rate of mortality and morbidity resulting from the death of a twin is 23-46%. 6 Major complications that may arise in the mother and the surviving fetus are disseminated intravascular coagulation, neurological and nephrological damage, and premature delivery and birth. 2 It is known that sudden hypotension in the dead fetus can trigger damage in the organ systems, notably the nervous system of the surviving twin in connection with the placental blood flow to the dead fetus.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, SUA via growth restriction was considered as the cause of the intrauterine loss [10]. Fetuses with sonographically diagnosed SUA were observed to have a high prevalence of structural anomalies and chromosomal abnormalities [10] but isolated SUA was not associated with aneuploidy [1,11]. If SUA occurs together with IUGR or other associated defects, because of the high risk of aneuploidy, parents should also be counselled for amniocentesis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several articles report cases of umbilical vein thrombosis. [11][12][13][14][15][16][17][18][19][20] Thrombosis was coupled with a varix in a few of these cases. 21,22 Rahemtullah et al 23 performed a retrospective study of 23 cases of umbilical vein varices, all of which were intra-abdominal.…”
Section: Discussionmentioning
confidence: 99%